ENGEMBANGAN E-MODUL MATERI KEANEKARAGAMAN HAYATI BERBASIS LITERASI SAINS BAGI SISWA SMA - Elfridei Br Purba; Mariani Natalina. L; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This development aims to produce an e-module of biodiversity material based on science literacy for high school students. This research was carried out at the FKIP Biology Education Study Program, Riau University, SMA Negeri 1 Pekanbaru from November 2021 to April 2022. The instruments used are validation sheets and response questionnaires. The validation sheet consists of 3 aspects, namely aspects of e-module format and graphics, aspects of content feasibility (presentation techniques and science literacy), and aspects of language assessment.. The results of the phase 1 limited trial obtained an average score of 3.82 with an excellent category. Meanwhile, the results of the phase 2 limited trial got an average score of 3.83 with an excellent category. The results of this study show that the e-module of biodiversity material is based on quality science literacy so that it can be used as a learning resource.Key Words: E-module, Science Literacy, Biodiversity